Barista Interpersonal Communication Strategy in Increasing Customer Satisfaction at Coffee Shop Titik Koma Matcha Club Multatuli Medan - Illahi Lubis, Hawa Nur; Indra, Farhan (Darul Yasin Al Sys, 2026)
The rapid expansion of the coffee shop industry has intensified competition in delivering superior customer experiences, positioning interpersonal communication as a critical determinant of customer satisfaction. Although previous studies have examined communication in service contexts, limited attention has been given to integrated service systems in which baristas simultaneously perform multiple service roles. This study aims to analyze barista interpersonal communication strategies and identify the supporting and inhibiting factors influencing their effectiveness at Titik Koma Matcha Club Coffee Shop, Medan. A qualitative descriptive approach was employed, with data collected through in-depth interviews, non-participatory observation, and documentation over a four-week period. Seven informants were selected using purposive sampling, consisting of two baristas, four customers, and one field supervisor. The analysis was grounded in DeVito’s five dimensions of interpersonal communication—openness, empathy, supportiveness, positiveness, and equality—and interpreted through customer satisfaction theory. The findings reveal that all five communication dimensions were consistently implemented across service stages, with empathy and openness emerging as the most influential factors in shaping customer satisfaction. Supporting factors included a positive work environment, continuous supervisory guidance, and an integrated service system that increased interaction intensity. Conversely, time constraints during peak hours limited communication depth, although this challenge was mitigated through structured task distribution. The study further demonstrates that effective interpersonal communication contributes to repeat visits and positive word-of-mouth behavior. This study concludes that interpersonal communication plays a strategic role as a core component of service quality in the coffee shop industry. These findings contribute to service communication literature and provide practical implications for developing communication-based service management strategies in customer-oriented food and beverage businesses.